SOSIALISASI KEWIRAUSAHAAN UNTUK MENINGKATKAN MINAT DAN MOTIVASI SISWA SMA CAHAYA KUDUS - Sutrisno Sutrisno (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
Entrepreneurial activities are activities that are one solution to earning income. In this service activity, the resource person carried out this activity at Cahaya Kudus High School, Muara Karang, North Jakarta. This theme was raised with the aim of providing knowledge and insight to students regarding how to do entrepreneurship in a simple way, providing motivation to students to become entrepreneurs throughtheir talents and field observations to find out the needs of society. This is also to erode the previous view which said that entrepreneurship is difficult, there will be many obstacles that arise, starting from capital problems, fear of trying, innovation and intention, so that in the end you experience failure. In fact, all of this can be overcome if the person has positive and creative thinking and prepares everythingcarefully, starting from planning, forming an ownership structure, selecting products and services as well as strategies for starting a business. In essence, entrepreneurship is simple. The obstacles that arise are caused internally. Make everything as simple as possible and don't get caught up in your own thoughts and heads.